2006
DOI: 10.2135/cropsci2005.04-0036-2
|View full text |Cite
|
Sign up to set email alerts
|

QTLs Associated with Resistance to Soybean Cyst Nematode in Soybean: Meta‐Analysis of QTL Locations

Abstract: Soybean cyst nematode (SCN) (Heterodera glycines Ichinohe) is the most important pest of soybean [Glycine max (L.) Merr.] in the world. A total of 17 quantitative trait locus (QTL) mapping papers and 62 marker–QTL associations have been reported for resistance to soybean cyst nematode in soybean. Conflicting results often occurred. The objectives of this study were to: (i) evaluate evidence for reported marker–QTL associations for resistance to SCN in soybean and (ii) extract relatively reliable and useful inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 52 publications
(96 reference statements)
2
105
0
9
Order By: Relevance
“…In some papers, the confidence interval was computed using a support interval that was either LODmax-1 or LODmax-2, but in most papers, the confidence interval was not given. To homogenize the data and estimate missing confidence intervals, a simpler solution was to use the empirical formula proposed by Darvasi and Soller (1997) for F 2 and BC and extended by Guo et al (2006) to other population types. For a BC, an F 2 or a DH population, the QTL confidence interval at the 95% level is 530/Nr 2 , where N is the population size and r 2 is the proportion of the total variance explained by the QTL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some papers, the confidence interval was computed using a support interval that was either LODmax-1 or LODmax-2, but in most papers, the confidence interval was not given. To homogenize the data and estimate missing confidence intervals, a simpler solution was to use the empirical formula proposed by Darvasi and Soller (1997) for F 2 and BC and extended by Guo et al (2006) to other population types. For a BC, an F 2 or a DH population, the QTL confidence interval at the 95% level is 530/Nr 2 , where N is the population size and r 2 is the proportion of the total variance explained by the QTL.…”
Section: Methodsmentioning
confidence: 99%
“…Software packages based on this methodology are available such as BioMercator (Arcade et al 2004) and Meta-QTL (Veyrieras et al 2007), a new software that removes some of the limitations of BioMercator in the number of QTLs it can handle at once. Meta-QTL analyses for flowering time in maize ), resistance to a nematode in soybean (Guo et al 2006), earliness in bread wheat (Hanocq et al 2007), and N uptake in maize (Coque et al 2008) have already shown the usefulness of this approach in determining the number of "true" QTLs underlying the observed QTLs and in positioning consensus QTLs with more precision. In rice, Norton et al (2008) conducted a study on root QTLs, but it was limited to the Azucena × Bala population and only three QTL clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-QTL analysis has also been successfully conducted in several other crops like maize Truntzler et al, 2010;Hao et al, 2010;Li et al, 2011;Wang et al, 2006;Coque et al, 2008), cotton (Rong et al, 2007), rice (Ballini et al, 2008;Norton et al, 2008;Khowaja et al, 2009), rapeseed (Shi et al, 2009), potato (Danan et al, 2011), cocoa (Lanaud et al, 2009), soybean (Guo et al, 2006;Sun et al, 2012) and apricot (Marandel et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Para avaliar a confiabilidade dos dados sobre mapeamento de QTLs disponíveis, Guo et al (2006) utilizaram as informações descritas acima em um estudo de metaanálise, baseado no intervalo de confiança. QTLs mapeados por diferentes trabalhos e QTLs significativos para diferentes raças de NCS foram agrupados quando seus intervalos de confiança foram sobrepostos e considerados como um mesmo lócus.…”
Section: Mapa Genético E Mapeamento De Qtl Em Sojaunclassified
“…Os QTLs mapeados para diferentes raças (1, 2, 3, 4, 5 e 14) foram agrupados nas mesmas regiões nos grupos A2, G, E, B1 e J. Por exemplo, o QTL do grupo de ligação G (rhg1) foi frequentemente, associado com resistência às raças 1, 2, 3 e 5 e o QTL no grupo A2 (Rhg4) é associado à resistência à raça 3 e, em alguns casos, com a resistência às raças 2, 5 e 14. Wu et al (2009), utilizando uma população grande de RILs (275 F 7:9 Essex x PI 437654), com boa cobertura do genoma (2.406 cM), intervalo médio de 8,7 cM e empregando o método de mapeamento por intervalo composto, identificaram os QTLs de efeito maior e já bem descritos GL A2, B1 e G e o QTL de pequeno efeito para resistência às raças 5 e 14, no grupo de ligação I (Sat_299-Sct_189) classificado como QTL sugestivo por Guo et al (2006). Além de confirmar essas regiões, quatro novos QTLs de pequeno efeito foram mapeados nos grupos H e K para a raça 1, no grupo C1 para a raça 3 e no grupo D1a para as raças 2 e 3.…”
Section: Mapa Genético E Mapeamento De Qtl Em Sojaunclassified